Effects of dietary lycopene and vitamin E on egg production, antioxidant status and cholesterol levels in Japanese Quail - Şahin, Nurhan; Şahin, Kazım; Onderci, M.; Karatepe, M.; Smith, M.O.; Küçük, Ömer (Asian-Australasian Association of Animal Production Societies, 2006)
Japanese Quails were used to evaluate the effects of dietary supplementation with vitamin E (dl-a-tocopheryl-acetate), lycopene, and their combination on egg production, egg quality, concentrations of malondialdehyde (MDA), vitamin E, A and cholesterol in serum and egg yolk. Quails (n = 120; 55 d old) were divided into four groups (n = 30/group) and fed a basal diet or the basal diet supplemented with lycopene (100 mg/kg diet), vitamin E (250 mg dl-?-tocopheryl-acetate/kg diet) or a combination of lycopene and vitamin E (100 mg/kg lycopene plus 250 mg dl-?-tocopheryl-acetate/kg diet). Vitamin E and lycopene did not affect (p>0.05) body weight, feed intake or egg weight. Egg production and Haugh unit were greater (p<0.05) in each supplemental group compared with the control group (p0.05). Serum and liver MDA levels were decreased in supplemented groups compared with the control group. Separately or as a combination, supplemental lycopene and vitamin E increased serum and egg yolk vitamin E and A but decreased cholesterol concentrations (p<0.05). In general, when a significant effect was found for a parameter, the magnitude of the responses to vitamin and lycopene supplements was greatest with the combination of the lycopene and vitamin E, rather than that observed with each supplement separately. Results of the present study indicate that supplementing with a combination of dietary lycopene and vitamin E reduced serum and yolk cholesterol concentrations and improved antioxidant status.
Keywords: Egg; Lycopene; MDA; Vitamin E